The Effectiveness of Regional Economic Development Planning in the 2024–2029 Regional Medium Term Development Plan of West Nusa Tenggara Province - Inang Karlina; Muhammad Ali; M. Ariy Dermawan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effectiveness of regional economic development planning as outlined in the 2024–2029 Regional Medium-Term Development Plan (RPJMD) of West Nusa Tenggara Province. The study focuses on three regional development priority sectors, namely poverty alleviation, food security enhancement, and tourism development as strategic sectors supporting regional economic growth. A qualitative approach with a descriptive method was employed to gain an in-depth understanding of the implementation of regional development planning. Data were collected through in-depth interviews, field observations, and document analysis of the RPJMD, regional government reports, data from the Central Statistics Agency (BPS), and relevant scientific literature. Informants were selected using purposive sampling and included officials from the Regional Development Planning Agency (Bappeda) of West Nusa Tenggara Province as well as academics with expertise in development planning. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. The findings indicate that the economic development planning contained in the West Nusa Tenggara RPJMD 2024–2029 has been systematically and integratively designed through an inclusive development approach based on local potential. Poverty alleviation policies have demonstrated positive progress, as reflected in the decline in the number of people living in poverty during the 2024–2025 period. In terms of food security, development policies have focused on improving food production, distribution, and downstream processing, although regional disparities remain evident. Meanwhile, the tourism sector has contributed to local economic growth through the development of tourism villages and the strengthening of community-based creative economies. The effectiveness of development planning is influenced by bureaucratic capacity, the quality of development data, inter-agency coordination, community participation, and the availability of regional financing support.